Residual stress measurement by strain gauge and X-ray diffraction method in different shaped rails. (February 2019) - Turan, Muhammet Emre; Aydin, Fatih; Sun, Yavuz; Cetin, Melik
Abstract: It is well known that rails are the most important part of railway infrastructure. Besides good wear and fatigue resistance, appropriate residual stress value in rails is required to improve performance of rails. The knowledge of residual stress types and distributions gives prediction the mechanical properties of materials for manufacturer. This study aims to make comparison between destructive and non-destructive residual stress measurement techniques and to investigate the influence of rail head geometry on residual stress by the use of two different quality rails. One of the rails is R260 grade and the other one is R260 grooved rail. In addition to residual stress measurement with strain gauge (cutting) and X-ray diffraction method, microstructures of the specimens were examined. Results show that grooved rail has higher residual stress and different types of stress were observed for samples which are supported by X-ray and strain gauge method. Highlights: R260 grooved rail has higher residual stress than that of R260 grade rails. Residual stress results about Strain gauge and X-ray diffraction techniques are consistent for two quality rails. Compressive residual stress can be observed on head part of R260 grooved rails. While R260 grooved rail has compressive residual stress, R260 grade has tensile residual stress.